2021
DOI: 10.1029/2020gl088872
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Predicting Intensity Change Using the Peak Time Lag Between Lightning and Wind in Tropical Cyclones

Abstract: The accurate forecasting of Tropical Cyclones (TCs) includes the most likely future path and intensity change. Although minimal improvement in intensity forecasts has been observed (Rappaport et al., 2009) compared with track forecasting, there has been a notable decrease in the intensity forecast error and an increase in intensity forecast skill (Cangialosi et al., 2020, Figure 3) over the past 2 decades. One of the difficulties of accurate forecasting is the lack of observations with adequate spatial and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Previous studies have found that the radial distribution of TC lightning shows an obvious pattern with two maxima in the inner core and outer rainbands and one minimum in the inner rainbands (Cecil et al, 2002;DeMaria et al, 2012;Stevenson et al, 2016). A positive correlation has been shown between lightning frequency and the maximum sustained wind speed of TCs (Price et al, 2009;Whittaker et al, 2015;Kong et al, 2021). The increase in lightning frequency may indicate the enhancement of TC intensity (Abarca et al, 2011;Pan et al, 2014;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies have found that the radial distribution of TC lightning shows an obvious pattern with two maxima in the inner core and outer rainbands and one minimum in the inner rainbands (Cecil et al, 2002;DeMaria et al, 2012;Stevenson et al, 2016). A positive correlation has been shown between lightning frequency and the maximum sustained wind speed of TCs (Price et al, 2009;Whittaker et al, 2015;Kong et al, 2021). The increase in lightning frequency may indicate the enhancement of TC intensity (Abarca et al, 2011;Pan et al, 2014;Wang et al, 2016).…”
Section: Introductionmentioning
confidence: 90%
“…The onset of increasing deep convection associated with low‐level circulation is an important process of TC genesis (Zehr, 1992). Several previous studies have suggested that the lightning activity may be an indicative precursor of the TC genesis and intensity (Price et al ., 2007, 2015; Jenkins and Pratt, 2008; Pan et al ., 2010; Kong et al ., 2021). Price et al .…”
Section: Introductionmentioning
confidence: 99%